Original paperOMEGA-3 SUPPLEMENTATION ATTENUATES THE PRODUCTION OF C-REACTIVE PROTEIN IN MILITARY PERSONNEL DURING 5 DAYS OF INTENSE PHYSICAL STRESS AND NUTRITIONAL RESTRICTION - Santos, E.P; Silva, A.S.; Costa, M.J.C.; Moura Junior, J.S.; Quirino, E.L.O.; Franca, G.A.M.; Asciutti, L.S.R. (Biology of Sport, 2012)
The effects of omega-3 (n-3) polyunsaturated fatty acid (PUFA) supplementation on the serum concentration of C-reactive protein (CRP) and activity of creatine kinase (CK) were investigated in military personnel. The concentrations of CRP and CK were used as inflammatory and muscle damage markers, respectively. Twenty subjects were divided into two groups and were given capsules containing either n-3 PUFA (SUP) (n=10) or placebo (PLA) (n=10) for four weeks. During the fourth week of supplementation, the subjects participated in a military boot camp that restricted both their calorie intake and rest, and increased their physical stress. Blood samples were taken in four instances: 1) pre-supplementation; 2) pre-camp; 3) during camp; 4) after camp. During the three weeks of supplementation and prior to boot camp, a significant reduction was observed in the serum concentration of CRP (50%) only in group SUP (p=0.04). Significant increases in CK activity of 103.9% in SUP (p=0.0001) and 225.5% in PLA (p=0.004) after camp confirmed the strenuous nature of this procedure. Serum CRP increased during camp in both groups but the SUP group presented a significantly lower concentration of CRP at the end of boot camp in comparison to the PLA group (6.18 ± 2.6 U · L-1 and 8.6 ± 2.1 U · L-1 for SUP and PLA respectively, when p=0.04). These results suggest that supplementation with n-3 PUFA can exhibit a protective effect against the inflammatory process induced by a regimen of intense physical stress and food restriction.